Clinical and Functional Outcomes Following Repeat VA-ECMO in Adults: A Propensity Score–Matched Comparative Study - Kostiantyn Kozakov; Alois Philipp; Maik Foltan; Henrik Heuer; Walter Petermichl; Alexander Dietl; Bernhard Flörchinger; Leopold Rupprecht; Simon Schopka; Christof Schmid; Zdenek Provaznik (Journal of Clinical Medicine, 2026)
Background/Objectives: Evidence on outcomes after repeat VA-ECMO in adults remains limited. This study aimed to compare survival and post-discharge functional outcomes between adults requiring a second VA-ECMO run and propensity-matched patients supported with a single VA-ECMO run and to characterize the clinical course during repeat support. Methods: This is an observational, single-center, retrospective cohort study with a propensity score–matched comparative analysis, conducted at a university tertiary-care referral center between 2006 and 2024. This study included 1496 adult patients (≥18 years) treated with VA-ECMO, of whom 30 (2.0%) required a second VA-ECMO run. Primary endpoints were in-hospital mortality, 30-day outcomes, and overall survival. Secondary exploratory analyses assessed baseline hemodynamic and metabolic parameters, multiorgan failure, neurological complications, and cannulation-related complications. Results: Repeat VA-ECMO was associated with longer support duration (median 6 vs. 4 days; p = 0.003) and a higher risk of MOF (OR 3.45; 95% CI 1.45–8.19; p = 0.003). No statistically significant differences in survival were observed (in-hospital mortality (OR 1.01; 95% CI, 0.48–2.11; p = 0.984); 30-day survival (OR 1.49; 95% CI, 0.72–3.07; p = 0.280); overall survival (OR 1.27; 95% CI, 0.59–2.73; p = 0.272). Repeat VA-ECMO was associated with higher transfusion requirements (RBC median 7.5 vs. 2 units; p < 0.001). After propensity matching, prolonged support, increased MOF, and higher transfusion burden persisted. ECOG outcomes were comparable overall; however, a borderline trend toward worse functional status was observed in patients undergoing repeat VA-ECMO during the same hospitalization (p = 0.057). Conclusions: Repeat VA-ECMO may be feasible in carefully selected adults, with no significant differences in survival, but is associated with prolonged support, increased transfusion requirements, and substantially higher MOF risk.